2021
DOI: 10.1002/adom.202101297
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Spatial Resolution, Fast Decay, and Stable X‐Ray Scintillation Screen through Assembling CsPbBr3 Nanocrystals Arrays in Anodized Aluminum Oxide

Abstract: A scintillation screen with ultrahigh spatial resolution, fast decay time, and high stability is the key to commercial application. Herein, a pixelated‐structure scintillation screen of CsPbBr3 nanocrystal arrays based on anodized aluminum oxide (AAO) is reported, and its scintillation properties for X‐ray imaging are explored. It is of note that ultrahigh spatial resolution (2 µm), fast photoluminescence decay time (9 ns), and high stability (>42 d) are successfully achieved by the pixelated CsPbBr3‐AAO ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Very recently, Li et al reported scintillators with a columnar structure, using AAO templates filled with CsPbBr 3 QDs, and observed a line spacing of 2 μm for JIMA patterns with a synchrotron X-ray source. 18 Note that many previous reports used higher X-ray energy and thicker scintillators, which was detrimental to the spatial resolution. We believe that one important reason for the high spatial resolution was that the CsPbBr 3 NW/array structure decreased the lateral spread of the scintillation light.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Li et al reported scintillators with a columnar structure, using AAO templates filled with CsPbBr 3 QDs, and observed a line spacing of 2 μm for JIMA patterns with a synchrotron X-ray source. 18 Note that many previous reports used higher X-ray energy and thicker scintillators, which was detrimental to the spatial resolution. We believe that one important reason for the high spatial resolution was that the CsPbBr 3 NW/array structure decreased the lateral spread of the scintillation light.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, CsPbBr 3 NCs embedded in Al 2 O 3 arrays have been shown to have significantly improved stability compared with conventional dense nanocrystalline thin films and X‐ray imaging capability with superior resolution of 250 lp mm −1 . [ 352 ] The pore diameter was 300 nm, with 20 μm pore depth. CsPbBr 3 NCs were prepared beforehand by the hot injection method and then incorporated into Al 2 O 3 arrays by negative pressure filling, forming a micropillar structure.…”
Section: Halide Perovskite Ncsmentioning
confidence: 99%
“…Perovskite nanocrystals (NCs), including CsPbBr 3 NCs, [ 19 , 20 , 21 , 22 , 23 , 24 ] MAPbBr 3 NCs (MA = CH 3 NH 3 + ), [ 25 , 26 ] and so on, [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] have displayed great potential as a new promising class of scintillators because of their many advantages such as strong X‐ray absorption ability, high RL intensity, fast light decay, and low‐cost solution synthesis. More importantly, compared with the big single crystal scintillators, [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] perovskite NCs scintillators are suitable for preparing thin scintillator films by using the promising bottom to up method due to their small sizes, quantum size effect, and tunable electronic bandgaps in the visible range.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many perovskite NCs‐based scintillators screen have been developed and show the potential for X‐ray imaging with the advantage of low‐cost, easy for preparation, and high detection sensitivity. [ 12 , 19 , 22 , 24 , 30 , 44 ] However, many scintillator films preparation methods [ 23 , 31 , 45 , 46 , 47 , 48 ] require the addition of auxiliary film‐forming geopolymers, which causes the low equivalent density of scintillator material in the film and thus results in the low RL intensity. To ensure the enough light output, the thick film is required but is usually opaque, which greatly increase the light scattering and seriously reduce the imaging resolution.…”
Section: Introductionmentioning
confidence: 99%